A Posteriori Error Estimate for Stabilized Low-Order Mixed FEM for the Stokes Equations (Advances in Applied Mathematics and Mechanics, 2021)
This paper is concerned with a stabilized approach to low-ordermixed finite element methods for the Stokes equations. We willprovide a posteriori error analysis for the method. We present two aposteriori error indicators which will be demonstrated to beglobally upper and locally lower bounds for the error of the finiteelement discretization. Finally two numerical experiments will becarried out to show the efficiency on constructing adaptive meshes.